Saturday's Child : Memoirs of Canada's First Female Cabinet Minister - Fairclough, Ellen Louks (Book collections on Project MUSE., 1995)
"Ellen Fairclough is perhaps best known as the first woman in Canada to become a federal cabinet minister." "Writing with the style and wit for which she was famous as a politician, Ellen Fairclough, now ninety, tells her story. Her reminiscences describe her early life, her efforts to become a business woman, and her experiences as a Progressive Conservative member for the constituency of Hamilton West (1950-63). Fairclough discusses the political factors that led to her appointment to the Diefenbaker cabinet, as well as other factors, including family values and the opportunities available in the bustling industrial city of Hamilton, that served as the context for her successes. While her story focuses on the politics involved, Fairclough also writes extensively about family life, friendships, and domestic detail. She attributes her success to the fact that she was a 'Saturday's child' who worked hard for what she achieved."--Jacket